Patellofemoral contact forces after ACL reconstruction: A longitudinal study - Williams, R. J.; Neal, K.; Alfayyaadh, A.; Khandha, A.; Manal, K.; Snyder-Mackler, L.; Buchanan, T. S. (Journal of Biomechanics, 2022)
Osteoarthritis (OA) development after ACL reconstruction (ACLR) is common. Patellofemoral OA after ACLR is as prevalent as tibiofemoral OA; however, few have explored the mechanisms leading to disease development in this compartment. Biomechanical alterations may be one mechanism responsible for post-traumatic knee OA. Patellofemoral contact forces during dynamic tasks, such as running and single leg hops, have been assessed at return to sport and later time points. The results of these studies, however, contradict each other, are only cross-sectional in nature, and are limited to specific points in time within the movement pattern. The purpose of this study was to assess patellofemoral contact forces 3, 6, and 24 months after ACLR during level walking over the entirety of the movement pattern. Patellofemoral contact forces were calculated after determination of muscle forces from a validated, subject-specific, EMG-driven neuromusculoskeletal model. Statistical parametric mapping was used to compare patellofemoral contact forces between limbs and across time points. Patellofemoral underloading of the involved limb (vs. uninvolved) was present at 3 months (p < 0.001 from 7 to 30% of stance) and 6 months (p = 0.001 from 11 to 23% of stance and p = 0.025 from 27 to 32%) after ACLR but was resolved by 24 months. Both limbs` load increased from 3 to 6 months. The involved limb displayed relatively consistent loads from 6 months onward, while the uninvolved limb`s decreased back down towards their 3-month values. Overall, these results suggest that early patellofemoral underloading exists after ACLR and may be leading to patellofemoral OA development.